‘I probably wouldn’t want to talk about anything too personal’: A qualitative exploration of how issues of privacy, confidentiality and surveillance in the home impact on access and engagement with online services and spaces for care-experienced young people - Stabler, Lorna; Cunningham, Emily; Mannay, Dawn; Boffey, Maria; Cummings, Aimee; Davies, Brittany; Wooders, Charlotte; Vaughan, Rachael; Evans, Rhiannon (Adoption & fostering, 2023)
This paper draws on a qualitative interview-based study that explored online mental health and wellbeing interventions and services for care-experienced young people. The study involved young people (n = 4), foster carers (n = 8), kinship carers (n = 2) and social care professionals (n = 9) in Wales, UK. The paper reflects on the complexities of online communication in the space of ‘the home’. It documents the ways in which care-experienced young people’s living arrangements can restrict access to services and complicate confidentiality within portals to the virtual world, creating an environment where young people and their carers ‘wouldn’t want to talk about anything too personal’. Drawing on data generated in a study focused on services and interventions to support the mental health and wellbeing of care-experienced children and young people, the paper considers privacy, confidentiality and surveillance in the home and reflects on how associated relational practices impact on care-experienced young people. While the data discussed in this paper was generated during the Covid-19 pandemic, its findings have implications for how care-experienced young people and their carers can be supported to engage with the digital world in the future. Plain Language Summary When mental health services are delivered online, they are usually accessed from home. Home can be different for young people who grow up in care, with records kept about their day-to-day activities, a lack of access to the digital world and policy governing how they are able to live their lives. We spoke with young people, foster carers and practitioners about what it is like for young people to access mental health services online. The paper discusses how the private home lives of care-experienced children and young people impacts on how they are able to access much needed mental health services. We look at the need to protect the freedom of children in care and care-experienced young people to take risks and access digital spaces like other children and teenagers do, while also recognising the reality of the pressures on practitioners and carers to protect looked after children from harm.